2022
DOI: 10.1111/iju.14859
|View full text |Cite
|
Sign up to set email alerts
|

GRade, Age, Nodes, and Tumor (GRANT) compared with Leibovich score to predict survival in localized renal cell carcinoma: A nationwide study

Abstract: To examine the performance of Leibovich score versus GRade, Age, Nodes, and Tumor score in predicting disease recurrence in renal cell carcinoma. Methods: In total, 7653 patients diagnosed with renal cell carcinoma from 2010 to 2018 were captured in the nationwide DaRenCa database; 2652 underwent radical or partial nephrectomy and had full datasets regarding the GRade, Age, Nodes, and Tumor score and Leibovich score. Discrimination was assessed with a Cox regression model. The results were evaluated with conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Detecting patients at high risk for RCC recurrence after curative treatment remains an unmet medical need. Many nomograms fail to this end, either due to the complexity of the nomogram or the low accuracy rate [ 35 ], [ 36 ]. Numerous biomarkers for RCC have demonstrated promising results in predicting recurrence-free survival, yet none have been validated and standardized for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Detecting patients at high risk for RCC recurrence after curative treatment remains an unmet medical need. Many nomograms fail to this end, either due to the complexity of the nomogram or the low accuracy rate [ 35 ], [ 36 ]. Numerous biomarkers for RCC have demonstrated promising results in predicting recurrence-free survival, yet none have been validated and standardized for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Several prognostic models incorporating clinical and pathological RCC variables have been validated to predict recurrence and mortality after nephrectomy in chRCC [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Of these, two models are recommended by European guidelines to predict cancer control outcomes after nephrectomy in non-metastatic chRCC [ 15 ]: Leibovich 2018 [ 2 , 16 ] and GRade, Age, Nodes and Tumor (GRANT) [ 3 , 16 , 17 , 18 , 19 , 20 ]. However, their ability to predict cancer-specific survival (CSS) has only been validated in a mono-institutional European cohort of 127 chRCC patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this article, Juul et al . compared GRANT system with Leibovich algorithm to evaluate which is more feasible to predict patient prognosis using the nationwide Danish RCC database 1 . They concluded that both Leibovich and GRANT system were useful in assessing recurrence and survival risk groups in clear and non‐clear cell RCC.…”
mentioning
confidence: 99%